Aerogel composite

KR103015826B1Active Publication Date: 2026-09-09LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020250058148
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-12-19
Filing Date
2025-05-02
Publication Date
2026-09-09
Estimated Expiration
2045-05-02

Smart Images

  • Figure 112025049913108-PAT00001_ABST
    Figure 112025049913108-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to an aerogel composite capable of maintaining high thermal insulation properties by exhibiting excellent thermal stability even when exposed to high-temperature environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an aerogel composite and its application as an insulating material. Background Technology

[0002] Aerogels are ultraporous materials with a high specific surface area (≥500 m²) having a porosity of approximately 90.0% to 99.9% and a pore size in the range of 1 nm to 100 nm. 2 As a material with a g content, it is a material possessing excellent properties such as ultralight weight, ultra-insulating insulation, and ultra-low dielectric strength. Accordingly, active research is being conducted not only on the development of aerogel materials but also on their application as transparent and eco-friendly high-temperature insulating materials, ultra-low dielectric thin films for high-density integrated devices, catalysts and catalyst supports, electrodes for supercapacitors, and electrode materials for seawater desalination.

[0003] The biggest advantage of aerogel is its super-insulation properties, which have a thermal conductivity of 0.300 W / m·K or less, lower than conventional organic insulation materials such as styrofoam.

[0004] Generally, aerogels are manufactured by producing a hydrogel from silica precursors such as water glass and alkoxysilane series (TEOS, TMOS, MTMS, etc.) and removing the liquid component inside the hydrogel without destroying the microstructure.

[0005] In particular, hydrophobic silica aerogel blankets, in which hydrophobic silica aerogel is formed on fibers, are widely used in construction or industrial sites as functional thermal insulation materials that prevent corrosion caused by moisture, and can also be usefully employed as thermal insulation or heat retention materials for aircraft, ships, automobiles, batteries, etc.

[0006] However, when aerogel blankets are used for the aforementioned purposes, or particularly when installed in high-temperature piping, they are often exposed to high-temperature environments for extended periods. In such cases, problems such as the collapse of the aerogel structure may occur as some components within the aerogel decompose or are lost. This issue can also occur when aerogel blankets are applied to battery modules inside automobiles; therefore, from a safety perspective, it is required that the blanket possess excellent thermal stability by minimizing the decomposition or loss of aerogel components even when exposed to high-temperature environments for a long time. The problem to be solved

[0007] One objective of the present invention is to provide an aerogel composite having excellent thermal stability even when exposed to a high-temperature environment for a long time.

[0008] However, the technical problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0009] According to one embodiment of the present invention, the aerogel composite comprises a fiber substrate including a plurality of discrete fibers and voids between the fibers; and a plurality of aerogel particles located on the fibers or in the voids between the fibers, and a silica aerogel having a network structure including one or more pores, wherein the weight retention rate measured after heating the aerogel composite at a temperature of 350°C for 60 minutes may be 96% or higher.

[0010] The weight retention rate measured after heating the above aerogel composite at a temperature of 350 °C for 5 minutes or 30 minutes may satisfy the following Equation 2:

[0011] [Equation 2]

[0012] A(%) = {(Weight retention rate measured after heating for x minutes (a)) - (Average value of weight retention rates after heating (b))} / (Average value of weight retention rates after heating (b)) X 100

[0013] In the above Equation 2, x is 5 minutes or 30 minutes, and the weight retention rate (a) measured after heating for x minutes is the percentage (%) of the weight of the aerogel composite measured after heating at a temperature of 350°C for x minutes relative to the weight of the aerogel composite before heating at 350°C, and the average value of the weight retention rates after heating (b) means the average value of the weight retention rates obtained after heating the aerogel composite at a temperature of 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes.

[0014] The above A may be a real number from -1.0 to +1.0, or a real number from -0.80 to +0.80.

[0015] The weight retention rate (a) of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes and 30 minutes, respectively, can satisfy Equation 2 above.

[0016] The weight retention rate (a) of the aerogel composite measured after heating the aerogel composite at 350°C for 5, 10, 15, 20, 25, and 30 minutes, respectively, can satisfy Equation 2 above.

[0017] The weight retention rate of the above aerogel composite measured after heating at a temperature of 350°C for 30 minutes may be 97% or higher.

[0018] When the above aerogel composite is heated at a temperature of 350 °C for 5 minutes and 60 minutes, the absolute value (B) of the change in weight retention rate of the aerogel composite per unit time can satisfy the following Equation 3:

[0019] [Equation 3]

[0020] B = |{(Weight retention rate measured after heating for y minutes) - (Weight retention rate measured after heating for z minutes)} / (y - z)|

[0021] In Equation 3 above, y is 5 minutes and z is 60 minutes; the weight retention rate measured after heating for y minutes is the percentage (%) of the weight of the aerogel composite measured after heating at 350 °C for y minutes relative to the weight of the aerogel composite before heating, and the weight retention rate measured after heating for z minutes is the percentage (%) of the weight of the aerogel composite measured after heating at 350 °C for z minutes relative to the weight of the aerogel composite before heating. Additionally, B is 1.0 X 10⁻⁶ -3 Up to 7.0 X 10 -2 It is a mistake.

[0022] The ratio of the total volume of the fibers per unit volume of the aerogel composite is 2 to 12%, and the ratio of the volume of the voids between the pore-containing aerogel and the dispersed fibers in the aerogel composite may be 88 to 98%.

[0023] The total volume ratio of the fibers per unit volume of the aerogel composite is 5 to 10%, and the volume ratio of the voids between the pore-containing aerogel and the dispersed fibers in the aerogel composite may be 90 to 95%.

[0024] The fiber substrate and the aerogel in the above aerogel composite may be included in a weight ratio of 1:0.4 to 2.

[0025] The above aerogel may be a silica aerogel.

[0026] The above aerogel may include one or more selected from the group consisting of silica, methylsilylated silica, dimethylsilylated silica, and trimethylsilylated silica.

[0027] The above aerogel composite may have a moisture impregnation rate (weight%) of 4 weight% or less for a specimen of size 100 mm X 100 mm represented by Formula 4 below:

[0028] [Equation 4]

[0029] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100

[0030] In the above Equation 4, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes.

[0031] The above aerogel composite may have a moisture impregnation rate (weight%) of 2 weight% or less for a specimen of size 10 mm X 10 mm represented by Formula 4.

[0032] According to another embodiment of the present invention, the invention relates to an insulating member comprising an aerogel composite provided in the present invention.

[0033] The above insulating member may further include a support member located on at least one of the upper and lower surfaces of the aerogel composite. Effects of the invention

[0034] The aerogel composite provided in the present invention has excellent high-temperature thermal stability, so even when exposed to a high-temperature environment for a long time, the degree of decomposition or loss of the aerogel components is not significant, and the amount of weight change over time at high temperatures is small, allowing the thermal insulation to be maintained at an excellent level. Brief explanation of the drawing

[0035] Figure 1 illustrates an example process of setting and extracting segmentation regions to analyze the volume share of fibers and the remaining parts excluding them within the aerogel composite using Dragonfly software after performing in-situ XRM analysis on the aerogel composite in Experimental Example 1. Figure 2 illustrates an example process of dividing the fibers and the remaining parts excluding the fibers within the area divided according to the contrast level using Dragonfly software in Experimental Example 1. Figure 3 illustrates an example process of calculating the volume share (volume ratio) of each region after dividing the fiber and the remaining parts excluding the fiber using Dragonfly software in Experimental Example 1. Specific details for implementing the invention

[0036] Hereinafter, the present invention will be described in more detail to aid in understanding the invention. In this case, terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0038] According to one embodiment of the present invention, the invention relates to an aerogel composite comprising a fiber substrate; and an aerogel having one or more pores.

[0039] The above "aerogel" comprises a plurality of primary aerogel particles having a size of approximately greater than 0 and less than 10 nm, greater than 0 and less than 5 nm, and secondary aerogel particles formed by the aggregation or bonding of these primary aerogel particles, and as a plurality of open pores are formed between the primary aerogel particles and between the secondary aerogel particles to form aggregates, the aerogel forms a three-dimensional network structure.

[0040] The above aerogel may be an inorganic silica aerogel formed from a silicon alkoxide-based compound or water glass as a precursor. As an example, the above aerogel may comprise one or more selected from the group consisting of silica, methylsilylated silica, dimethylsilylated silica, and trimethylsilylated silica. As another example, the above aerogel may have at least some of the SiO2 on the surface and / or inside the pores of the SiO2 network structure having a bonding structure of Si-O-SiO2(CH3), Si-O-SiO(CH3)2, or Si-O-Si(CH3)3. The specific manufacturing process of the silica aerogel is described in detail below.

[0041] Aerogel particles may be located on the fiber substrate or in the pores between adjacent fiber substrates, preferably on the fiber substrate and in the pores between adjacent fiber substrates. The "aerogel particles" are particles in the form of individual solid units constituting the aerogel, and may include primary aerogel particles having a size of approximately greater than 0 and less than 10 nm, or greater than 0 and less than 5 nm, preferably around 1 nm, and secondary aerogel particles formed by the aggregation of these particles. However, the aerogel within the aerogel composite is mostly in the form of secondary aerogel particles or aggregated and bonded thereof, and a small amount of primary aerogel particles that do not form secondary aerogel particles may be mixed in. The above secondary aerogel particles may have an average particle size of approximately 5 to 2,000 nm, 5 to 1,000 nm, 5 to 500 nm, 5 to 100 nm, or 5 to 50 nm, but are not limited thereto. The average particle size may be measured by any means known to those skilled in the art, such as scanning electron microscopy, dynamic light scattering, optical microscopy, or size exclusion methods, but is not limited thereto.

[0042] The aerogel may have a skeletal structure including mesopores, and in addition to the mesopores, may include micropores or macropores. Here, the "mesopore" is a pore with an average pore diameter in the range of about 2 nm to about 50 nm, the "macropore" is a pore with an average pore diameter exceeding about 50 nm, and the "micropore" is a pore with an average pore diameter less than about 2 nm. The aerogel may contain at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%, or 100% mesopores of the pore volume of the skeletal structure. In one embodiment, the aerogel may include mesopores. In one specific example, the aerogel may include mesopores and micropores. The pore size may be measured by any means known to those skilled in the art, such as gas adsorption experiments, mercury infiltration, capillary flow porometry, or positron annihilation lifetime spectroscopy (PALS), but is not limited thereto.

[0043] The porosity of the above aerogel may be 80% or more, 85% or more, 88% or more, 89% or more, 90% or more, 91% or more, 92% or more, 93% or more, 94% or more, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and preferably 80% or more and 99.9% or less, but is not limited thereto.

[0044] The above-described aerogel composite has a structure in which at least some of a plurality of aerogel particles are dispersed, preferably bonded, on the surface of a substrate containing fibers, and at the same time, at least some of a plurality of aerogel particles are dispersed, preferably located, in the empty spaces between the discrete fibers within the substrate. Examples of the substrate may be discrete fibers, films, sheets, nets, fibers, porous bodies, foams, nonwoven fabrics, or laminates of two or more layers thereof. Additionally, depending on the application, the surface may have a surface roughness or be patterned.

[0045] The above fiber substrates are polyester, polyolefin terephthalate, poly(ethylene) naphthalate, polycarbonate (e.g., rayon, nylon), cotton (e.g., Lycra from DuPont), carbon (e.g., graphite), polyacrylonitrile (PAN), PAN oxide, non-carbonized heat-treated PAN (e.g., from SGL Carbon), glass fiber-based materials (S-glass, 901 glass, 902 glass, 475 glass, E-glass, etc.), silica-based fibers, e.g., quartz (e.g., Saint-Gobain Quartzel), Q-felt (from Johns Manville), Saffil, Durablanket (from Uniplex), and other silica fibers, Duraback (from carborundum), polyaramid fibers, e.g., Kevlar, Nomex, Sontera (all from DuPont), Conex (from Tyzine), polyolefins, e.g., Tyvek (from DuPont), Dyneema (from DSM), Spectra (made by Honeywell), other polypropylene fibers, such as Typar and Xavan (both made by DuPont), fluoropolymers, such as PTFE under the trade name Teflon (made by DuPont), Goretex (made by WL GORE), silicon carbide fibers, such as Nicalcon (made by COI Ceramics), ceramic fibers, such as Nextel (made by 3M), ceramic paper, acrylic polymers, wool, silk, hemp, leather, suede fibers, PBO-Xylon fibers (made by Tyobo), liquid crystal materials, such as Vectan (made by Hoechst), Cambrel fibers (made by DuPont), polyurethane, polyamide, wool fibers, basalt fibers, boron, aluminum, iron, stainless steel fibers, or other thermoplastic resins such as PEEK, PES, PET, PEK, PPS, etc., may be included, but any fiber that can further improve thermal insulation performance by including a space or void where the insertion of aerogel is easy may be used without limitation. As an example, the fiber substrate may include glass fibers.As another example, the fiber substrate may be made of glass fiber, but is not limited thereto.

[0046] The thickness of the fiber substrate may be 0.1 to 20 mm, but is not limited thereto.

[0047] The above aerogel composite may have a rectangular shape in which a fiber substrate and aerogel are mixed from the top surface to the bottom surface, but is not limited thereto.

[0048] In addition, at least a portion of the upper or lower surface of the aerogel composite, preferably the entire surface, may have a flat shape. Here, the "flat shape" means that no irregularities are formed by intentional embossing or coating processes. Forming the upper and lower surfaces of the aerogel composite flat as described above can improve ease of operation when laminating support members, such as sheets, onto the upper and lower surfaces in the future, and can increase the adhesion retention rate of the support members. Furthermore, it is desirable to reduce friction with adjacent equipment surfaces even when the aerogel composite itself is applied directly as an insulating material without support members.

[0049] The thickness of the above aerogel composite may be 0.05 to 20 mm, for example 0.1 to 15 mm, 0.1 to 10 mm, or 0.1 to 5 mm, but is not limited thereto.

[0050] The density of the above aerogel composite is 0.05 to 0.50 g / cm³ 3 , 0.05 to 0.35 g / cm² 3 , 0.05 to 0.30 g / cm² 3 , 0.10 to 0.30 g / cm² 3 or 0.15 to 0.30 g / cm² 3 It may be, but is not limited to this.

[0051] The aerogel composite provided in the present invention includes an aerogel and pores in a specific volume ratio or larger, excluding the fibers, in particular, so that the aerogel forms a rigid pore structure, and excellent thermal insulation can be secured through these pores and pores. Furthermore, even when exposed to high temperatures of 350°C or higher for a long time, there is little structural change in the aerogel or pores, and the degree of hydrophobization inside the pores and pores is high, so that thermal insulation is not degraded and is maintained at an excellent level even in high-temperature environments.

[0052] Specifically, the remaining portion excluding the fibers per unit volume of the aerogel composite, that is, the volume ratio of the voids between the aerogel containing pores and the dispersed fibers, may be 85% or more, 86% or more, 87% or more, 88% or more, 89% or more, or 90% or more, and 98% or less, 97% or less, 96% or less, 95% or less, 94% or less, or 93% or less, and preferably 88 to 98%, or 90 to 95%.

[0053] The volume ratio of the fibers per unit volume of the aerogel composite may be 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, or 10% or more, and 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less, and preferably 2 to 12%, or 5 to 10%.

[0054] However, the unit volume of the aerogel composite mentioned above refers to the volume of an aerogel composite in the shape of a rectangular prism with dimensions of 1 cm x 1 cm. The unit volume of the aerogel composite refers to the volume of an aerogel composite in the shape of a rectangular prism with dimensions of 1 cm x 1 cm. In this case, the volume of the aerogel composite refers to the volume obtained by multiplying the width x length x thickness of the aerogel composite, assuming that an arbitrary material fills the area where aerogel particles are not filled, such as the pores within the aerogel or the voids between dispersed fibers. The volume of fibers per unit volume of the aerogel composite refers to the sum of the volumes occupied by individual fibers included in the unit volume of the aerogel composite. The volume of the remaining area excluding fibers per unit volume of the aerogel composite includes the volume of the aerogel containing pores and the voids between dispersed fibers. In this case, the volume of the pores and voids can be calculated by assuming that an arbitrary material is filled flatly into the pores and voids. The volume of the void between the aerogel containing pores and the fibers per unit volume of the above aerogel composite can be calculated by subtracting the volume of the fibers alone from the unit volume of the aerogel composite.

[0055] The volume ratio of the aerogel containing pores and voids per unit volume of the aerogel composite described above may be obtained by randomly obtaining a total of five rectangular specimens from the aerogel composite, with a width x length of 1 cm x 1 cm and a height equal to the thickness of the aerogel composite, and then calculating the average value of the volume ratio of the aerogel containing pores and voids per unit volume of the aerogel composite measured from each specimen. In this case, the five specimens may be obtained by arbitrarily placing four specimens at a position 10 cm away from each corner of the aerogel composite manufactured in a rectangular shape (e.g., 60 cm x 12 cm in size, but not limited thereto) in the center of the specimen, and by placing one specimen at the center of the aerogel composite.

[0056] In addition, the volume ratio of the aerogel containing pores and voids per unit volume of the above-described aerogel composite can be measured by placing an aerogel composite specimen on a DEBEN load cell, performing in situ XRM analysis using a ZEISS VERSA 520 instrument, and measuring the volume ratio of the fibers and the remaining parts excluding the fibers in the segmentation area to be analyzed using Dragonfly software (version 2021.3). At this time, the size of the analysis area (width x length x height) is not specifically limited and can be set and extracted to be less than or equal to each size of the unit volume; for example, it can be set and extracted so that the width x length x height is approximately 1700μm x 1600μm x 500μm. However, the above-described method is described for reference as an example of a method for measuring the volume ratio of the voids between the aerogel containing pores and the fibers per unit volume of the above-described aerogel composite, and is not limited to the above-described method.

[0057] In addition, after heating the aerogel composite at a temperature of 200°C for 1 hour, the remaining portion excluding the fibers per unit volume of the heat-treated aerogel composite, that is, the volume ratio of the voids between the aerogel and the fibers containing pores, may be 83% or more, 84% or more, 85% or more, 86% or more, 87% or more, 88% or more, 89% or more, 90% or more, and 98% or less, 97% or less, 96% or less, 95% or less, 94% or less, 93% or less, 92% or less, 91% or less, or 90% or less, and preferably may be 85 to 98%, 88 to 98%, or 90 to 95%.

[0058] In addition, after heating the aerogel composite at a temperature of 200°C for 1 hour, the volume ratio of the fibers per unit volume of the heat-treated aerogel composite may be 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, 9% or more, 10% or more, 11% or more, 12% or more, and 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, 11% or less, or 10% or less, and preferably may be 2 to 15%, 2 to 12%, or 5 to 10%.

[0059] After heating the above aerogel composite at a temperature of 200°C for 1 hour, the volume ratio of the voids between the aerogel containing pores and the dispersed fibers based on the unit volume of the aerogel composite may be 0.8 to 1.5 times, 0.8 to 1.3 times, 0.8 to 1.2 times, 0.9 to 1.2 times, or 0.9 to 1.1 times the volume ratio of the aerogel containing pores and the dispersed fibers based on the unit volume of the aerogel composite before heating.

[0060] In addition, the above-mentioned aerogel composite can produce an excellent thermal insulation effect at both room temperature and high temperature by including an amount of aerogel greater than a specific ratio relative to the fiber substrate.

[0061] Specifically, the aerogel composite may contain at least 0.35 times, at least 0.4 times, or at least 0.45 times the weight of the fiber substrate, and for example, may contain the fiber substrate and the aerogel in a weight ratio of 1:0.35 to 2, and preferably may contain them in a weight ratio of 1:0.4 to 2, or 1:0.4 to 1, or 1:0.45 to 1.

[0062] Even when the above aerogel composite is exposed to temperatures of 350°C or higher for a long period of time of more than one hour, the weight retention rate of the aerogel composite is high and remains constant within a specific range, so the thermal insulation performance can also be maintained at an excellent level without significant degradation.

[0063] In this specification, the "weight retention rate" refers to the ratio of the weight of the aerogel composite measured after heating at a temperature of 350°C for a predetermined time to the weight of the aerogel composite before heating, expressed as a percentage as shown in Equation 1 below. Here, the above-mentioned predetermined time may be, for example, 1 minute or more, 5 minutes or more, 10 minutes or more, 20 minutes or more, 25 minutes or more, 30 minutes or more, 40 minutes or more, 50 minutes or more, 60 minutes or more, 70 minutes or more, 80 minutes or more, 90 minutes or more, 2 hours or more, 4 hours or more, or 6 hours or more, and 12 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 90 minutes or less, 80 minutes or less, 70 minutes or less, 60 minutes or less, 40 minutes or less, 30 minutes or less, 20 minutes or less, 10 minutes or less, or 5 minutes or less; as one example, it may be 5 minutes to 30 minutes, and as another example, it may be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes, but is not limited thereto.

[0064] [Equation 1]

[0065] Weight retention rate (wt%) of aerogel composite after heating = {(Weight of aerogel composite after heating) / (Weight of aerogel composite before heating)} X 100

[0066] The weight retention rate measured after heating the above aerogel composite at a temperature of 350 °C for any one of a continuous time selected from 5 to 30 minutes may satisfy the following Equation 2:

[0067] [Equation 2]

[0068] A (%) = {(Weight retention rate measured after heating for x minutes (a)) - (Average value of weight retention rates after heating (b))} / (Average value of weight retention rates after heating (b)) X 100

[0069] In the above Equation 2, "x minutes" means any one of a continuous duration of 5 minutes to 30 minutes. For example, x minutes may be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes, but is not limited thereto.

[0070] In addition, the "weight retention rate (a)" measured after heating for x minutes refers to the percentage (%) of the weight of the aerogel composite measured after heating at a temperature of 350°C for x minutes relative to the weight of the aerogel composite before heating at 350°C according to Equation 1.

[0071] In addition, the "average value of weight retention rates after heating (b)" refers to the average value of weight retention rates of an aerogel composite obtained after heating the aerogel composite at a temperature of 350°C for at least two consecutive hours selected from 5 minutes to 30 minutes. As an example, it may refer to the average value of weight retention rates of an aerogel composite obtained after heating the aerogel composite at 350°C for at least two selected times selected from 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes relative to the weight of the aerogel composite before heating.

[0072] The above A (%) is -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, -0.75 to +0.75, -0.70 to +0.70, -0.65 to +0.65, -0.60 to +0.60, -0.55 to +0.55, -0.50 to +0.50, -0.45 to +0.45, -0.40 to +0.40, -0.35 to +0.35, -0.30 to +0.30, -0.25 to +0.25, -0.20 to +0.20, - It may be a real number in the range of 0.15 to +0.15, or -0.10 to +0.10.

[0073] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5, 10, 15, 20, 25, or 30 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may mean the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for at least two times selected from 5, 10, 15, 20, 25, and 30 minutes.

[0074] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes or 30 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may mean the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for at least two times selected from 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes.

[0075] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes and 30 minutes, respectively, may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may mean the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for at least two times selected from 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes.

[0076] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, -0.75 to +0.75, -0.70 to +0.70, -0.65 to +0.65, 0 to +1.0, 0 to +0.95, 0 to +0.90, 0 to +0.85, 0 to +0.80, 0 to +0.75, 0 to +0.70, or 0 to +0.65.

[0077] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 10 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -0.80 to +0.80, -0.75 to +0.75, -0.70 to +0.70, -0.65 to +0.65, -0.60 to +0.60, -0.55 to +0.55, -0.50 to +0.50, -0.45 to +0.45, 0 to +0.80, 0 to +0.75, 0 to +0.70, 0 to +0.65, 0 to +0.60, 0 to +0.55, 0 to +0.50, or 0 to +0.45.

[0078] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 15 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -0.60 to +0.60, -0.55 to +0.55, -0.50 to +0.50, -0.45 to +0.45, -0.40 to +0.40, -0.35 to +0.35, -0.30 to +0.30, -0.25 to +0.25, or -0.20 to +0.20.

[0079] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 20 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -0.50 to +0.50, -0.45 to +0.45, -0.40 to +0.40, -0.35 to +0.35, -0.30 to +0.30, -0.25 to +0.25, -0.20 to +0.20, -0.15 to +0.15, -0.10 to +0.10, -0.50 to 0, -0.45 to 0, -0.40 to 0, -0.35 to 0, -0.30 to 0, -0.25 to 0, -0.20 to 0, -0.15 to 0, or -0.10 to 0.

[0080] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 25 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -0.80 to +0.80, -0.75 to +0.75, -0.70 to +0.70, -0.65 to +0.65, -0.60 to +0.60, -0.55 to +0.55, -0.50 to +0.50, -0.80 to 0, -0.75 to 0, -0.70 to 0, -0.65 to 0, -0.60 to 0, -0.55 to 0, or -0.50 to 0.

[0081] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 30 minutes may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. At this time, the above A (%) may be a real number within the range of -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, -0.75 to +0.75, -1.0 to 0, -0.95 to 0, -0.90 to 0, -0.85 to 0, -0.80 to 0, or -0.75 to 0.

[0082] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes or 30 minutes, respectively, may satisfy Equation 2 above. In this case, the average value (b) of the weight retention rates after heating may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. In this case, A (%) may be a real number within the range of -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, or -0.75 to +0.75.

[0083] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5 minutes and 30 minutes, respectively, may satisfy Equation 2 above. In this case, the average value of the weight retention rates after heating (b) may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, respectively. In this case, A (%) may be a real number within the range of -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, or -0.75 to +0.75.

[0084] As an example, the weight retention rate of the aerogel composite measured after heating the aerogel composite at 350°C for 5, 10, 15, 20, 25, and 30 minutes, respectively, may satisfy Equation 2 above. In this case, the average value (b) of the weight retention rates after heating may refer to the average value of the weight retention rates of the aerogel composite obtained after heating the aerogel composite at 350°C for 5, 10, 15, 20, 25, and 30 minutes, respectively. In this case, A (%) may be a real number within the range of -1.0 to +1.0, -0.95 to +0.95, -0.90 to +0.90, -0.85 to +0.85, -0.80 to +0.80, or -0.75 to +0.75.

[0085] In addition, when heating the aerogel composite to a temperature of 350°C, the absolute value (B) of the change in weight retention rate of the aerogel composite per unit time can satisfy Equation 3 below.

[0086] [Equation 3]

[0087] B = |{(Weight retention rate measured after heating for y minutes) - (Weight retention rate measured after heating for z minutes)} / (y - z)|

[0088] In the above Equation 3, y and z are each independently selected time values ​​from a continuous period of 5 to 60 minutes, and are different values. In this case, the unit of time may be 'minutes'.

[0089] In addition, the "weight retention rate measured after heating for y minutes" and the "weight retention rate measured after heating for z minutes" refer to the percentage (%) of the weight of the aerogel composite measured after heating the aerogel composite at a temperature of 350°C for y minutes or z minutes relative to the weight of the aerogel composite before heating according to Equation 1.

[0090] In addition, the above B is 1.0 X 10 -3 Up to 7.0 X 10 -2 , 1.5 X 10 -3 Up to 7.0 X 10 -2 , 1.0 X 10 -3 Up to 6.5 x 10 -2 , 1.5 X 10 -3 Up to 6.5 x 10 -2 , 1.0 X 10 -3 Up to 6.0 X 10 -2 , 1.5 X 10 -3 Up to 6.0 X 10 -2 , 2.0 X 10 -3 Up to 6.0 X 10 -2 , 2.5 X 10 -3 Up to 6.0 X 10 -2 , 3.0 X 10 -3 Up to 6.0 X 10 -2 , 3.5 X 10 -3 Up to 6.0 X 10 -2 , 4.0 X 10 -3 Up to 6.0 X 10 -2 , 1.0 X 10 -3Up to 5.5 X 10 -2 , 1.5 X 10 -3 Up to 5.5 X 10 -2 , 2.0 X 10 -3 Up to 5.5 X 10 -2 , 2.5 X 10 -3 Up to 5.5 X 10 -2 , 3.0 X 10 -3 Up to 5.5 X 10 -2 , 3.5 X 10 -3 Up to 5.5 X 10 -2 , or 4.0 X 10 -3 Up to 5.5 X 10 -2 It can be a real number within the range.

[0091] As an example, in Equation 3 above, y may be 5 minutes and z may be 30 minutes; or y may be 30 minutes and z may be 5 minutes. In this case, B is 3.0 x 10 -3 Up to 7.0 X 10 -2 , 3.5 X 10 -3 Up to 7.0 X 10 -2 , 4.0 X 10 -3 Up to 7.0 X 10 -2 , 4.0 X 10 -3 Up to 6.5 x 10 -2 , 4.5 X 10 -3 Up to 6.5 x 10 -2 , 5.0 X 10 -3 Up to 6.5 x 10 -2 , 5.0 X 10 -3 Up to 6.0 X 10 -2 , 5.5 X 10 -3 Up to 6.0 X 10 -2 , or 6.0 X 10 -3 Up to 5.5 X 10 -2 It could be a mistake.

[0092] As an example, in Equation 3 above, y may be 5 minutes and z may be 40 minutes; or y may be 40 minutes and z may be 5 minutes. In this case, B is 2.0 x 10 -3 Up to 7.0 X 10 -2, 2.5 X 10 -3 Up to 7.0 X 10 -2 , 3.0 X 10 -3 Up to 7.0 X 10 -2 , 3.0 X 10 -3 Up to 6.5 x 10 -2 , 3.5 X 10 -3 Up to 6.5 x 10 -2 , 4.0 X 10 -3 Up to 6.5 x 10 -2 , 4.0 X 10 -3 Up to 6.0 X 10 -2 , 4.5 X 10 -3 Up to 6.0 X 10 -2 , 5.0 X 10 -3 Up to 6.0 X 10 -2 , 5.0 X 10 -3 Up to 5.5 X 10 -2 , or 5.0 X 10 -3 Up to 5.0 X 10 -2 It could be a mistake.

[0093] As an example, in Equation 3 above, y may be 5 minutes and z may be 50 minutes; or y may be 50 minutes and z may be 5 minutes. In this case, B is 1.5 x 10 -3 Up to 6.0 X 10 -2 , 2.0 X 10 -3 Up to 6.0 X 10 -2 , 2.5 X 10 -3 Up to 6.0 X 10 -2 , 2.5 X 10 -3 Up to 5.5 X 10 -2 , 3.0 X 10 -3 Up to 5.5 X 10 -2 , 3.5 X 10 -3 Up to 5.5 X 10 -2 , 3.5 X 10 -3 Up to 5.0 X 10 -2 , 3.5 X 10 -3 Up to 4.5 x 10 -2 , 3.5 X 10 -3 Up to 4.0 X 10 -2, 4.0 X 10 -3 Up to 3.5 x 10 -2 , or 4.0 X 10 -3 Up to 3.0 X 10 -2 It could be a mistake.

[0094] As an example, in Equation 3 above, y may be 5 minutes and z may be 60 minutes; or y may be 60 minutes and z may be 5 minutes. In this case, B is 1.0 x 10 -3 Up to 6.0 X 10 -2 , 1.5 X 10 -3 Up to 6.0 X 10 -2 , 2.0 X 10 -3 Up to 6.0 X 10 -2 , 2.0 X 10 -3 Up to 5.5 X 10 -2 , 2.5 X 10 -3 Up to 5.5 X 10 -2 , 2.5 X 10 -3 Up to 5.5 X 10 -2 , 3.0 X 10 -3 Up to 5.5 X 10 -2 , 3.0 X 10 -3 Up to 5.0 X 10 -2 , 3.0 X 10 -3 Up to 4.5 x 10 -2 , or 3.0 X 10 -3 Up to 4.0 X 10 -2 It could be a mistake.

[0095] The above aerogel composite may have a weight retention rate of 97% or more, 98% or more, or 99% or more as measured after heating at 350°C for 30 minutes.

[0096] The above aerogel composite may have a weight retention rate of 96% or more, 97% or more, 98% or more, or 99% or more as measured after heating at 350°C for 60 minutes.

[0097] In order to exclude the influence of moisture on the aerogel composite when measuring the change in thermal stability, i.e., weight retention rate, of the aerogel composite while maintaining the above aerogel composite at a high temperature of 350 ℃ for a predetermined time, a pre-heat treatment can be performed at 150 ℃ for 1 hour.

[0098] In the above aerogel composite, the moisture impregnation rate (weight%) represented by Formula 4 below may be 5 weight% or less.

[0099] [Equation 4]

[0100] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100

[0101] In the above Equation 4, the water impregnation rate can be calculated by floating a specimen of the aerogel composite on distilled water at 21±2 ℃, placing a 6.4 mm mesh screen over the specimen and sinking it to 127 mm below the water surface for impregnation, removing the mesh screen after 15 minutes, and when the specimen floats, picking it up with a clamp and suspending it vertically for 60 ± 5 seconds, then measuring the weight before and after impregnation to determine the weight increase rate. Here, a lower water impregnation rate indicates a higher degree of hydrophobicity of the aerogel composite.

[0102] Surface water repellency and cross-sectional water repellency, used to evaluate the hydrophobicity on the surface and the hydrophobicity inside the aerogel composite, respectively, can both be measured using Equation 4 above, and can be measured by varying the specimen used. Specifically, when measuring the moisture impregnation rate, the moisture impregnation rate measured using a relatively large aerogel composite specimen of 100 mm x 100 mm, which is similar in size to a commercially used aerogel blanket, is defined as the water repellency on the surface of the aerogel composite. A low surface moisture impregnation rate indicates a high degree of hydrophobicity on the surface of the aerogel composite. The surface water repellency of the aerogel composite calculated through Equation 4 above may be 5 weight% or less, preferably 4 weight% or less.

[0103] In addition, when measuring the moisture impregnation rate, the moisture impregnation rate measured using an aerogel composite specimen cut into relatively small sizes, for example, 10 mm x 10 mm, is defined as the water repellency at the cross-section of the aerogel composite. A low cross-sectional moisture impregnation rate implies that the degree of hydrophobicity is high not only on the surface of the aerogel composite but also within it. The cross-sectional water repellency of the aerogel composite calculated through Equation 4 above may be 2 weight% or less, preferably 1.5 weight% or less.

[0104] The above aerogel composite may have a thermal conductivity at room temperature (23±5 ℃) of 30.0 mW / mK or less, 25.0 mW / mK or less, or 20.0 mW / mK or less, preferably 15.0 mW / mK or less, and within this range, the thermal insulation of the aerogel composite can be maximized.

[0105] The above aerogel composite may have a high temperature (150 ℃) thermal conductivity of 35.0 mW / mK or less, 30.0 mW / mK or less, or 25.0 mW / mK or less, and within this range, the thermal insulation of the aerogel composite can be maximized.

[0106] The above aerogel composite may have excellent mechanical strength, with a compressive strength at 10% strain of 20 kPa to 80 kPa, 20 kPa to 70 kPa, 30 kPa to 80 kPa, 30 kPa to 70 kPa, 35 kPa to 80 kPa, or 35 kPa to 70 kPa. Here, the compressive strength may be measured by preparing a specimen according to ASTM C165.

[0107] The above aerogel composite has a tensile strength of 30 N / cm 2 up to 60 N / cm 2 , 40 N / cm 2 Up to 55 N / cm 2 , or 45 N / cm 2 Up to 55 N / cm 2 As such, it may have excellent flexibility. Here, the tensile strength may be measured by manufacturing a specimen according to ASTM D638 standards.

[0108] In the present invention, the aerogel composite may generally be formed by a step of preparing a silica sol; a step of gelling after impregnating a fiber substrate with the silica sol; and a drying step. Each step is described below. However, the specific manufacturing processes or examples described herein are not intended to limit any specific type of aerogel or its manufacturing method. This specification may include any aerogel formed by any associated manufacturing method known to a person skilled in the art.

[0109] Silica sol preparation steps

[0110] In the present invention, a silica sol can be prepared by mixing a silica precursor composition and a catalyst composition.

[0111] The above silica precursor composition may include water and / or a polar organic solvent in the silica precursor.

[0112] The above silica precursor can be any precursor that can be used to form a silica aerogel without limitation, and may be, for example, a silicon-containing alkoxide-based compound. Specifically, tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), methyl triethyl orthosilicate, dimethyl diethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrasecondary butyl orthosilicate, tetra tertiary butyl orthosilicate, tetrahexyl orthosilicate, and tetracyclohexyl orthosilicate. It may be a tetraalkyl silicate such as tetradodecyl orthosilicate, tetradodecyl orthosilicate, etc. More specifically among these, the silica precursor may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), or a mixture thereof.

[0113] In addition, the silica precursor may be a water glass solution. Here, the water glass solution may refer to a diluted solution obtained by adding distilled water to water glass and mixing it, and the water glass may be sodium silicate (Na2SiO3), which is an alkali silicate obtained by melting silicon dioxide (SiO2) and an alkali.

[0114] In addition, the silica precursor may include pre-hydrolyzed TEOS (HTEOS). HTEOS is an ethyl silicate oligomer material with a broad molecular weight distribution, and since it can control physical properties such as gelation time when synthesized from TEOS monomers in the form of an oligomer, it can be easily applied according to the user's reaction conditions. Furthermore, it has the advantage of producing reproducible physical properties of the final product. The HTEOS may generally be synthesized by a condensation reaction of TEOS that has undergone a partial hydration step under acidic conditions. That is, the HTEOS may be in the form of an oligomer prepared by condensing TEOS, and the oligomer may be partially hydrated.

[0115] The silica concentration of the above silica precursor composition is 10 kg / m³ 3 up to 100 kg / m² 3 , 20 kg / m 3 up to 80 kg / m² 3 , 30 kg / m 3 up to 70 kg / m² 3 , 30 kg / m 3 up to 60 kg / m² 3 , or 35 kg / m² 3 Up to 45 kg / m 3 It may be, but is not limited thereto. The above silica concentration is the concentration of silica contained in the silica precursor relative to the silica precursor composition, and can be appropriately adjusted by varying the content of the silica precursor, organic solvent, and water.

[0116] The above silica precursor may be used in an amount such that the silica content contained in the silica sol is 0.1% by weight to 30% by weight, but is not limited thereto. If the silica content satisfies the above range, it is desirable in terms of securing excellent mechanical properties, particularly flexibility, of the aerogel composite while also having an improved thermal insulation effect.

[0117] The above polar organic solvent may include alcohols, specifically examples of which include monohydric alcohols such as methanol, ethanol, isopropanol, butanol, etc.; polyhydric alcohols such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, etc.; or combinations thereof, but other solvents known to those skilled in the art may also be used without limitation. Among these, the polar organic solvent may be a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, butanol, etc., such as ethanol, when considering miscibility with water and aerogel.

[0118] The above polar organic solvent can be used in an appropriate amount by a person skilled in the art, taking into account the degree of hydrophobicity in the final aerogel composite while promoting the surface modification reaction.

[0119] In order to prepare a fully hydrolyzed silica precursor when preparing the above silica precursor composition, the silica precursor and water may be mixed in a molar ratio of 1:0.5 to 10, 1:1 to 8, or 1:3 to 6, but are not limited thereto.

[0120] In addition, when preparing the above silica precursor composition, if a silica precursor that has been fully hydrolyzed into a silica precursor (e.g., fully hydrolyzed TEOS) is included, in order to satisfy the silica concentration, the silica precursor (e.g., fully hydrolyzed TEOS) and an organic solvent may be mixed in a weight ratio of 1:0.5 to 5, preferably 1:0.5 to 3.5, but are not limited thereto.

[0121] The weight ratio of the above-mentioned fully hydrolyzed silica precursor and the organic solvent can be appropriately adjusted within the above range so that the weight ratio of the fiber substrate to the aerogel in the finally manufactured aerogel composite is 1:0.35 to 2, preferably 1:0.4 to 2, or 1:0.4 to 1, more preferably 1:0.45 to 1.

[0122] The above silica precursor composition may further include an acid catalyst, specifically, when an alkoxysilane compound other than a hydrolysate is used as a precursor, the acid catalyst may further include an acid catalyst. In this case, any acid catalyst that lowers the pH to 3 or lower can be used without limitation, and examples include hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, oxalic acid, or acetic acid. In this case, the acid catalyst may be added in an amount that lowers the pH of the sol to 3 or lower, or it may be added in the form of an aqueous solution dissolved in an aqueous solvent.

[0123] The above catalyst composition may include an inorganic base such as sodium hydroxide or potassium hydroxide as a base catalyst; or an organic base such as ammonium hydroxide. Specific examples include sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), ammonium hydroxide (NH4OH; ammonia solution), tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), methylamine, ethylamine, isopropylamine, monoisopropylamine, diethylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, triisopropylamine, tributylamine, choline, monoethanolamine, diethanolamine, 2-aminoethanol, 2-(ethylamino)ethanol, 2-(methylamino)ethanol, N-methyl diethanolamine, dimethylaminoethanol, diethylaminoethanol, nitrilotriethanol, It may be 2-(2-aminoethoxy)ethanol, 1-amino-2-propanol, triethanolamine, monopropanolamine, dibutanolamine, pyridine, or a combination thereof, but is not limited thereto.

[0124] The above base catalyst may be included in an amount such that the pH of the sol becomes 5 to 9. If the pH of the sol falls outside this range, gelation may not be easy or the gelation rate may become excessively slow, potentially leading to reduced processability. Additionally, since the base may precipitate when added in a solid state, it may be preferable to add it in a solution diluted by an aqueous solvent or the aforementioned organic solvent. In this case, the dilution ratio of the base catalyst and the organic solvent, specifically the alcohol, may be 1:4 to 1:100 by volume, but is not limited thereto.

[0125] To prepare the silica sol, the silica precursor composition and the catalyst composition may be mixed in a volume ratio of 1:0.01 to 10.0, 1:0.01 to 5.0, or 1:0.01 to 2.0, but are not limited thereto.

[0126] When preparing the above silica sol, silica aerogel powder containing one or more organic functional groups is added together with the above silica precursor so that hydrophobic groups can exist even inside the pores during aerogel gelation, thereby increasing the hydrophobicity retention power, especially at high temperatures.

[0127] The above-mentioned aerogel powder can be manufactured by preparing a silica sol using an alkoxysilane such as tetraethyl orthosilicate (TEOS), gelling it, performing surface modification with a surface modifier such as alkyltrichlorosilane such as methyltrichlorosilane; dialkyldichlorosilane such as dimethyldichlorosilane; trialkylchlorosilane such as trimethylchlorosilane; symmetric disiloxane or hexaalkyldisiloxane such as hexamethyldisiloxane; trialkylalthoxysilane such as trimethylethoxysilane; or silazane such as hexamethyldisilazane, and then sequentially performing supercritical drying and atmospheric pressure drying processes. Here, the composition of the silica precursor, catalyst composition, and organic solvent for preparing the silica sol, as well as the gelation conditions, overlap with the manufacturing process of the aerogel composite according to the present invention, so a detailed description thereof is omitted below.

[0128] The average particle size of the above aerogel powder may be 10 to 100 μm, preferably 10 to 60 μm, but is not limited thereto.

[0129] To achieve the above objective, the aerogel powder may be added in an amount of 5 to 30 parts by weight, preferably 5 to 15 parts by weight, per 100 parts by weight of silica contained in the silica sol. If the amount of aerogel powder added is less than the above range, it is difficult to expect the desired effect, and if it exceeds the above range, the strength of the aerogel composite may decrease.

[0130] Additionally, additives may be added to the silica sol as needed. In this case, any known additives that can be added when manufacturing an aerogel may be used, and for example, additives such as opacifiers and flame retardants may be used.

[0131] The above additive may be added in an amount of 0.1% to 10% by weight, 0.1% to 7% by weight, 0.5% to 7% by weight, or 0.5% to 5% by weight with respect to the silica content of the aerogel, but is not limited thereto.

[0132] Gelation step of silica sol

[0133] In the present invention, silica sol can be impregnated into a substrate and then gelled.

[0134] The above impregnation process is a process that allows the catalytic silica sol to penetrate into the internal pores of the substrate. It can be performed by introducing the catalytic silica sol and the substrate into a reaction vessel, or by spraying the catalytic silica sol onto the substrate moving on a conveyor belt according to a roll-to-roll process. At this time, to improve the bonding between the substrate and the silica sol, the substrate can be lightly pressed to ensure sufficient impregnation. Subsequently, the material can be pressed to a certain thickness under a constant pressure to remove excess silica sol, thereby reducing the drying time.

[0135] The temperature of the silica sol in the reaction vessel may be 10 to 40 ℃, 20 to 40 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 45 ℃. It is preferable that the temperature of the silica sol in the reaction vessel satisfies the above range, as the aforementioned viscosity range of the catalyzed sol can be achieved more easily and the desired level of viscosity range can be satisfied even with a relatively short residence time.

[0136] The above-mentioned catalytic silica sol can be impregnated into a substrate in a volume ratio of 0.1 to 10:1 (catalytic silica sol:substrate), 0.1 to 1:1, 0.3 to 1:1, 0.5 to 1:1, or 0.6 to 1:1, and preferably in a volume ratio of 1:1, but is not limited thereto.

[0137] The silica sol impregnated in the substrate can be gelled simultaneously with the impregnation process of the silica sol or sequentially after the impregnation process.

[0138] In this specification, the term "gelation" may refer to a sol-gel reaction, and the term "sol-gel reaction" may refer to forming a network structure from a silicon unit precursor material. Here, the network structure may refer to a planar net-like structure formed by connecting specific polygons having one or more types of atomic arrangements, or a structure that forms a three-dimensional skeletal structure by sharing vertices, edges, faces, etc., of specific polyhedra.

[0139] The substrate impregnated with the above-mentioned catalystd sol can be gelled on a moving element such as a conveyor belt.

[0140] The above gelation can be performed under an ambient atmosphere temperature of 20 to 40 ℃, 25 to 40 ℃, 30 to 40 ℃, or 35 to 40 ℃ on the conveyor belt, and it is particularly preferable to perform it under an ambient atmosphere temperature of 30 to 40 ℃ or 35 to 40 ℃, as this can increase the aerogel and pore strength.

[0141] In addition, the gelation time may be performed for 1 to 120 minutes, 1 to 100 minutes, 1 to 60 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 40 minutes, 10 to 30 minutes, or 10 to 20 minutes, but is not limited thereto.

[0142] Aging stage of the gelled wet gel complex

[0143] In the present invention, if necessary, an aging step may be further included to allow the wet gel composite obtained by gelation as described above to be left at an appropriate temperature so that chemical changes are completely completed. In the aging step, the network structure formed by gelation can be formed more firmly, thereby improving the mechanical stability of the aerogel composite.

[0144] The above aging step can be performed by leaving the gelled wet gel complex as is at an appropriate temperature, or by adding a cross-linking promoting compound.

[0145] In addition, during the aging step, the process may be carried out in the presence of the wet gel complex by adding a solution of a base catalyst, such as sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), triethylamine, or pyridine, diluted in an organic solvent to a concentration of 1 to 10%. In this case, Si-O-Si bonds within the aerogel are induced to the maximum extent, making the network structure of the silica gel more robust and facilitating the maintenance of the pore structure during the subsequent drying process. At this time, the organic solvent may be the aforementioned alcohol, and specifically, may include ethanol.

[0146] The above aging step can be carried out by leaving the product at a temperature of 30 to 80 ℃, 40 to 80 ℃, or 50 to 80 ℃ for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours to strengthen the pore structure, and within this range, it is possible to prevent a decrease in productivity while preventing the loss of solvent due to evaporation, thereby preventing an increase in production costs.

[0147] In addition, the above aging step may be performed by first aging at 30 to 80 ℃ for 0.1 to 5 hours to strengthen the pore structure, and then second aging may be performed at 30 to 80 ℃ for 0.1 to 20 hours, 0.5 to 15 hours, 0.5 to 10 hours, 0.5 to 7 hours, or 1 to 5 hours in the presence of a solution in which a base catalyst is diluted in an organic solvent to a concentration of 1 to 10%.

[0148] The above aging step may be performed in a separate reaction vessel after recovering the gelled wet gel complex, or it may be performed inside the reaction vessel where the gelling step was performed.

[0149] Surface modification step of the wet gel complex

[0150] The present invention may further include a surface modification step in which the surface of the wet gel composite obtained by gelation as described above or the aged wet gel composite is hydrophobized in the presence of a surface modifier, if necessary.

[0151] The above surface modifier may be any compound that hydrophobicizes the wet gel surface without limitation, such as a silane compound, a siloxane compound, a silanol compound, a silazane compound, or a combination thereof. Specific examples include silane compounds comprising trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane, 3-aminopropyltriethoxysilane, etc.; and siloxane compounds comprising polydimethylsiloxane, polydiethylsiloxane, or octamethylcyclotetrasiloxane, etc. Silanol-based compounds including trimethylsilanol, triethylsilanol, triphenylsilanol, and t-butyldimethylsilanol, etc.; silazane-based compounds including 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane, or 1,2-diisopropyldisilazane, etc.; or a combination thereof, but not limited thereto.

[0152] The above surface modifier may be used as a solution diluted in an organic solvent. Here, the organic solvent may be an alcohol (organic solvent), and the surface modifier may be diluted to 1 to 15 volume% based on the total volume of the diluted solution.

[0153] In addition, the above surface modifier may be added in an amount of 0.01 to 90 volume% with respect to the wet gel composite for a sufficient surface modification effect, but is not limited thereto.

[0154] The surface modification step may be performed for 1 to 24 hours at a temperature of 50 to 90 ℃ or 50 to 80 ℃, but is not limited thereto.

[0155] Drying step (or drying and surface modification step)

[0156] The present invention may include a drying step of drying a wet gel complex to obtain an aerogel complex.

[0157] The above drying is performed as a process that removes only the solvent while maintaining the pore structure of the aged gel, and can be performed, for example, by supercritical drying and / or atmospheric pressure drying.

[0158] The above supercritical drying process is performed using supercritical carbon dioxide. For example, a matured wet gel complex is placed into a supercritical drying reactor, and then liquid CO2 is filled and a solvent exchange process is performed to replace the alcohol solvent inside the wet gel with CO2. Afterward, the temperature is raised to 40 to 70 ℃ at a constant heating rate, e.g., 0.1 ℃ / min to 1 ℃ / min. Then, a pressure greater than the pressure at which carbon dioxide reaches a supercritical state, e.g. 100 bar to 150 bar, is maintained to maintain the carbon dioxide in a supercritical state for a certain period of time, specifically 20 minutes to 1 hour. Generally, carbon dioxide reaches a supercritical state at a temperature of 31 ℃ and a pressure of 73.8 bar. An aerogel composite can be manufactured by maintaining the carbon dioxide at a constant temperature and constant pressure for 2 to 12 hours, more specifically 2 to 6 hours, and then gradually removing the pressure to complete the supercritical drying process, but is not limited thereto.

[0159] In addition, the above atmospheric pressure drying process may be carried out according to conventional methods such as hot air drying or IR drying at a temperature of 70 to 200 ℃ and atmospheric pressure (1±0.3 atm), but is not limited thereto.

[0160] However, the present invention may include not only a method for drying a surface-modified wet gel composite, but also a method for performing surface modification during supercritical drying of an aged or unaged wet gel composite.

[0161] When surface modification is performed during supercritical drying as described above, a surface modifying agent may be added at a point where the solvent extraction rate during supercritical drying is 70 wt% or more, 75 wt% or more, or 80 wt% or more. By adding a surface modifying agent when the solvent extraction rate in the supercritical extractor falls within the above-mentioned range, the aerogel composite can have excellent hydrophobicity, and in particular, an aerogel composite with excellent hydrophobicity retention ability can be produced even under high-temperature environments.

[0162] Here, the "solvent extraction rate" is the ratio of the amount of solvent recovered from the bottom of the extractor during the supercritical drying step to the total amount of solvent contained in the wet gel complex, and can be calculated by the following Equation 5.

[0163] [Equation 5]

[0164] Solvent Extraction Rate (%) = {(Amount of solvent discharged and recovered from the extractor) / (Amount of solvent in the wet gel complex fed into the extractor)} X 100 (%)

[0165] In the above Equation 5, the weight of the solvent discharged and recovered from the extractor is the weight of the solvent obtained from the extraction solvent separator after drying, and the total amount of solvent contained in the wet gel complex is the difference between the weight of the aerogel complex after drying and the weight of the wet gel complex before drying.

[0166] In the present invention, the surface modifier may be any compound that hydrophobicizes the wet gel surface without limitation, such as a silane-based compound, a siloxane-based compound, a silanol-based compound, a silazane-based compound, or a combination thereof. Specific examples include silane compounds comprising trimethylchlorosilane (TMCS), dimethyldimethoxysilane, dimethyldiethoxysilane, methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), trimethylethoxysilane (TMES), vinyltrimethoxysilane, ethyltriethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane, tetraethoxysilane, dimethyldichlorosilane, 3-aminopropyltriethoxysilane, etc.; and siloxane compounds comprising polydimethylsiloxane, polydiethylsiloxane, or octamethylcyclotetrasiloxane, etc. Silanol-based compounds including trimethylsilanol, triethylsilanol, triphenylsilanol, and t-butyldimethylsilanol, etc.; silazane-based compounds including 1,2-diethyldisilazane, 1,1,2,2-tetramethyldisilazane, 1,1,3,3-tetramethyldisilazane, 1,1,1,2,2,2-hexamethyldisilazane (HMDS), 1,1,2,2-tetraethyldisilazane, or 1,2-diisopropyldisilazane, etc.; or a combination thereof, but not limited thereto.

[0167] The above surface modifier may be added in an amount of 1 to 20 parts by weight, preferably 5 to 15 parts by weight, per 100 parts by weight of the wet gel, but is not limited thereto. Here, the wet gel refers to the weight of the wet gel itself, excluding the weight of the fiber substrate.

[0168] The solvent used during the supercritical drying described above may be the solvent previously used in the preparation of the wet gel composite, and may include water and an organic solvent. Additionally, the organic solvent may specifically be an alcohol, wherein the alcohol may be a monohydric alcohol such as methanol, ethanol, isopropanol, butanol, etc.; or a polyhydric alcohol such as glycerol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, and sorbitol, etc., and any one or more of these may be used. Among these, considering the miscibility with water and aerogel, a monohydric alcohol having 1 to 6 carbon atoms, such as methanol, ethanol, isopropanol, butanol, etc., preferably ethanol, may be used.

[0169] In addition, the solvent may comprise 85 to 95 weight% of an organic solvent and 5 to 15 weight% of water.

[0170] In addition, when introducing the wet gel complex into the supercritical extractor during the supercritical drying process, it is desirable to introduce the wet gel complex at a volume of 50% or more based on 100% of the volume of the supercritical extractor, as this creates an environment where even the residual solvent can be converted to a supercritical state when the surface modifier is subsequently introduced.

[0171] It is preferable that the drying step, which includes the above-described silica sol preparation step, impregnation step, and surface modification step, be designed such that the volume ratio of fibers per unit volume of the aerogel composite produced after final drying is 2 to 12% or 5 to 10%, and the volume ratio of the voids between the pore-containing aerogel and the dispersed fibers, as the remaining portion excluding the fibers, is 88 to 98% or 90 to 95%, and additionally, the aerogel composite is designed such that the fiber substrate and the aerogel are included in a weight ratio of 1:0.4 to 2, preferably 1:0.4 to 1, or 1:0.45 to 1. It is desirable that the fibers and the pore-containing aerogel are included in the aerogel composite in the above-described volume ratios, as this provides excellent thermal insulation and excellent hydrophobicity even within the pores or voids, thereby providing excellent ability to withstand high temperatures, i.e., excellent thermal stability.

[0172] As such, the aerogel composite provided in the present invention has excellent high-temperature thermal insulation properties, so when applied as an insulating material to high-temperature pipes or battery modules of electric vehicles, it can exhibit excellent heat blocking capabilities.

[0174] According to another embodiment of the present invention, the invention relates to an insulating member comprising an aerogel composite provided in the present invention.

[0175] The above-described insulating member may include the aerogel composite described above and a supporting member located on at least one of the two sides of the aerogel composite.

[0176] Examples of the above-mentioned support members include film-type support members, sheet-type support members, thin-film support members, porous support members, etc.

[0177] The above film-like support member is formed by molding a polymer raw material into a thin film, and examples include organic films such as PET (polyethylene terephthalate), polyester, PC (polycarbonate), PI (polyimide), PEN (polyethylene naphthalate), PEEK (polyether ether ketone), PAR (polyarylate), PCO (polycylicolefin), polynorbornene, PES (polyethersulphone), and COP (cycloolefin polymer), glass films, etc. (metal deposition films are also included).

[0178] The above sheet-like support member is formed from organic, inorganic, or metal fiber-like raw materials, and examples include paper, non-woven fabric (including glass mats), organic fiber fabric, glass cloth, etc.

[0179] The above-mentioned thin film support member is formed by molding a metal raw material into a thin film, and examples include aluminum foil, copper foil, etc.

[0180] The above porous support member has a porous structure made of organic, inorganic, or metal raw materials, and examples include porous organic materials (e.g., polyurethane foam), porous inorganic materials (e.g., zeolite sheets), porous metal materials (e.g., porous metal sheets, porous aluminum sheets), etc.

[0181] The above support member may be a single layer, or a multi-layer structure of two or more layers.

[0182] The thickness of the above-mentioned support member is not particularly limited and may be, for example, 0.1 to 100 μm, or 1 to 50 μm.

[0183] In addition, the present invention may further include an adhesive layer or an adhesive layer between the exposed surface of the aerogel composite and the supporting member.

[0184] The above adhesive layer or adhesive layer may include, but is not limited to, an acrylic adhesive, a polyurethane adhesive, an olefin adhesive, an SBR rubber adhesive, or a silicone adhesive.

[0185] The above adhesive layer or adhesive layer is not particularly limited and, for example, may be 1 to 100 μm, or 10 to 50 μm.

[0186] The above-mentioned insulating material can also be applied for purposes such as insulation, heat blocking, or flame retardant in the construction, aviation, automotive, battery, home appliance, semiconductor, and industrial facilities sectors.

[0188] According to another embodiment of the present invention, the invention relates to a battery module or battery pack comprising an aerogel composite according to the present invention.

[0189] The battery module may include a module case having an internal space and one or more battery cells existing within the internal space. The number of battery cells accommodated in the module case is not limited in any specific way and can be adjusted according to the application of the battery module. The battery cells accommodated in the module case may be electrically connected to one another. The type of battery cell accommodated in the module case is not limited, but, for example, the battery module may include cylindrical, prismatic, or pouch-type case battery cells.

[0190] The battery module may include an aerogel composite according to the present disclosure within the module case of the battery module. The aerogel composite may be positioned between battery cells accommodated within the module case. The aerogel composite may be positioned between the module case and a plurality of battery cells, i.e., around the module case. The aerogel composite positioned within the module case may act as an insulator to reduce heat propagation within the battery module and improve the safety of the battery module.

[0191] The battery pack may include one or more of the battery modules. In the battery pack, the battery modules may be electrically connected to each other. The battery pack may include an aerogel composite according to the present disclosure. For example, the aerogel composite may be located between the battery modules of the battery pack. The aerogel composite may also at least partially surround a plurality of battery modules within the battery pack. The aerogel composite may act as an insulating material within the battery pack to reduce heat propagation and improve the safety of the battery pack.

[0193] The present invention will be explained in detail below through the following examples. However, the following examples are merely illustrative of the present invention, and the scope of the present invention is not limited by the following examples.

[0195] Examples

[0197] [Preparation Example 1] Preparation of Aerogel Powder

[0198] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.67 to the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 to the obtained silica sol. The catalyzed sol was placed in a container to proceed with gelation. To the wet gel after gelation was complete, a solution of trimethylethoxysilane (TMES) diluted in ethanol (2 vol%) was added as a surface modifier at 90 vol% based on the volume of the wet gel, and surface modification was performed at a temperature of 75 ℃ for 12 hours. At this stage, to increase the surface modification efficiency, the wet gel in monolithic form can be fragmented into pieces several cm in size before proceeding with surface modification. After the surface modification was completed, the wet gel was placed in a 70L supercritical extractor, and CO2 was injected at 28°C and 70 bar at a rate of 70 L / min for 10 minutes. Subsequently, the temperature inside the extractor was raised to 50°C over 1 hour and 20 minutes, and upon reaching 50°C and 150 bar, CO2 was injected continuously at a rate of 5 L / min for 20 minutes. During this process, ethanol was recovered through the bottom of the separator. Supercritical drying was performed by injecting CO2 continuously at a rate of 5 L / min again for 20 minutes after a 20-minute rest period. Afterward, CO2 was vented over a period of 2 hours, and the silica aerogel was prepared. The prepared silica aerogel was ground using a RETSCH ZM 200 Ultra Centrifugal Mill to produce hydrophobic aerogel powder classified to have an average particle size in the range of 10 to 100 μm.

[0200] [Example 1] Preparation of an Aerogel Composite

[0201] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:0.73 to the hydrated TEOS solution. Subsequently, the prepared aerogel powder was added to the prepared silica sol in an amount of 10 parts by weight per 100 parts by weight of silica in the silica sol. A base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 was added to the obtained silica sol to prepare a catalyzed sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 30°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 5 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 85% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0203] [Example 2] Preparation of an Aerogel Composite

[0204] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.1 with the hydrated TEOS solution. Subsequently, the prepared aerogel powder was added to the prepared silica sol in an amount of 15 parts by weight per 100 parts by weight of silica in the silica sol. A base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 was added to the obtained silica sol to prepare a catalyzed sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 40°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 10 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 75% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0206] [Example 3] Preparation of an Aerogel Composite

[0207] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.5 with the hydrated TEOS solution. Subsequently, the prepared aerogel powder was added to the prepared silica sol in an amount of 5 parts by weight per 100 parts by weight of silica in the silica sol. A base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 was added to the obtained silica sol to prepare a catalyzed sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 5 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 70% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0209] [Example 4] Preparation of an Aerogel Composite

[0210] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.33 to the hydrated TEOS solution. Subsequently, the prepared aerogel powder was added to the prepared silica sol in an amount of 5 parts by weight per 100 parts by weight of silica in the silica sol. A base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 was added to the obtained silica sol to prepare a catalyzed sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 40°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 5 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 75% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0212] [Example 5] Preparation of an Aerogel Composite

[0213] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.4 to the hydrated TEOS solution. Subsequently, prepared aerogel powder was added to the prepared silica sol in an amount of 10 parts by weight per 100 parts by weight of silica in the silica sol. A base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 was added to the obtained silica sol to prepare a catalyzed sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 35°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 10 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 80% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0215] [Comparative Example 1] Preparation of an aerogel composite

[0216] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:2 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 to the obtained silica sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated into a fiber (glass fiber mat, 5 mm) as a substrate. The fiber, having passed through the impregnation tank and been infiltrated with the catalyzed sol, passed over a conveyor belt at a constant speed and gelled. During this process, the ambient temperature on the conveyor belt was maintained at 30°C. A hexamethyldisilazane (HMDS) / ethanol solution (1:19 volume ratio) was added to the wet gel complex as a surface modifier at 80 volume% based on the volume of the wet gel complex, and surface modification was performed at a temperature of 70°C for 3 hours. After the completion of surface modification, the wet gel complex was placed in a 70L supercritical extractor, and CO2 was injected at 28°C and 70 bar at a rate of 70 L / min for 10 minutes. Subsequently, the temperature inside the extractor was raised to 50°C over 1 hour and 20 minutes, and upon reaching 50°C and 150 bar, CO2 was injected continuously at a rate of 5 L / min for 20 minutes. During this process, ethanol was recovered through the bottom of the separator. Supercritical drying was performed by injecting CO2 continuously at a rate of 5 L / min again for 20 minutes after a 20-minute rest period. Afterwards, CO2 was vented for 2 hours, and a silica aerogel composite was prepared.

[0218] [Comparative Example 2] Preparation of an aerogel composite

[0219] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:1.25 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 to the obtained silica sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated into a fiber (glass fiber mat, 5 mm) as a substrate in a volume ratio of 1:1. The fiber, having passed through the impregnation tank and been infiltrated with the catalyzed sol, passed over a conveyor belt at a constant speed and gelled. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. After placing the prepared wet gel composite into a supercritical extractor, the temperature was raised to 70°C and the pressure to 150 bar, and the temperature was maintained for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 5 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 60% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. The supercritical drying process took a total of 4 hours. Afterward, the aerogel composite was prepared by further drying at atmospheric pressure in an oven at 150°C.

[0221] [Comparative Example 3] Preparation of an aerogel composite

[0222] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:2.05 with the hydrated TEOS solution. Subsequently, the prepared aerogel powder was added to the prepared silica sol in an amount of 3 parts by weight per 100 parts by weight of silica in the silica sol. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 with the obtained silica sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated onto a fiber (glass fiber mat, 5 mm) as a substrate. Fibers infiltrated with the catalyzed sol after passing through an impregnation tank were gelled while moving along a conveyor belt at a constant speed. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. The prepared wet gel composite was introduced into a supercritical extractor, heated to 70°C and pressurized to 150 bar, and maintained at these temperatures for 20 minutes. Subsequently, supercritical carbon dioxide was continuously injected for 20 minutes to extract the solvent, followed by a resting period of 20 minutes. The supercritical carbon dioxide injection and resting process was repeated one more time, and after the third continuous injection of supercritical carbon dioxide, hexamethyldisilazane (HMDS) was added at a ratio of 3 parts by weight based on 100 parts by weight of the wet gel. The solvent extraction rate upon the addition of hexamethyldisilazane was 70% by weight. After maintaining a resting state for 20 minutes, supercritical carbon dioxide was continuously injected. Subsequently, the pressure was reduced to atmospheric pressure, and supercritical drying was completed. At this time, supercritical drying took a total of 4 hours. Afterwards, the aerogel composite was prepared by additional atmospheric pressure drying in an oven at 150°C.

[0224] [Comparative Example 4] Preparation of an aerogel composite

[0225] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:2.6 with the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 to the obtained silica sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated into a fiber (glass fiber mat, 5 mm) as a substrate in a volume ratio of 1:1. The fiber, having passed through the impregnation tank and been infiltrated with the catalyzed sol, passed over a conveyor belt at a constant speed and gelled. During this process, the ambient temperature on the conveyor belt was maintained at 25°C. A hexamethyldisilazane (HMDS) / ethanol solution (1:19 volume ratio) was added to the wet gel complex as a surface modifier at 80 volume% based on the volume of the wet gel complex, and surface modification was performed at a temperature of 70°C for 4 hours. After the completion of surface modification, the wet gel complex was placed in a 70L supercritical extractor, and CO2 was injected at 28°C and 70 bar at a rate of 70 L / min for 10 minutes. Subsequently, the temperature inside the extractor was raised to 50°C over 1 hour and 20 minutes, and upon reaching 50°C and 150 bar, CO2 was injected continuously at a rate of 5 L / min for 20 minutes. During this process, ethanol was recovered through the bottom of the separator. Supercritical drying was performed by injecting CO2 continuously at a rate of 5 L / min again for 20 minutes after a 20-minute rest period. Afterwards, CO2 was vented for 2 hours, and a silica aerogel composite was prepared.

[0227] [Comparative Example 5] Preparation of an aerogel composite

[0228] A silica precursor solution was prepared by mixing tetraethyl orthosilicate (TEOS) and water in a molar ratio of 1:4 and adding ethanol in a weight ratio of 1:1 with TEOS. To promote the hydrolysis of the silica precursor solution, an acid was added to lower the pH of the silica precursor solution to 3 or lower, and the mixture was stirred for at least 2 hours to prepare a hydrated TEOS solution. A silica sol was prepared by adding ethanol in a weight ratio of 1:3.4 to the hydrated TEOS solution. A catalyzed sol was prepared by adding a base catalyst solution (5 wt% NaOH aqueous solution) in a volume ratio of 99:1 to the obtained silica sol. After filling an impregnation tank with this catalyzed sol, the catalyzed sol was impregnated into a fiber (glass fiber mat, 5 mm) as a substrate in a volume ratio of 1:1. The fiber, having passed through the impregnation tank and been infiltrated with the catalyzed sol, passed over a conveyor belt at a constant speed and gelled. During this process, the ambient temperature on the conveyor belt was maintained at 20°C. A hexamethyldisilazane (HMDS) / ethanol solution (1:19 volume ratio) was added to the wet gel complex as a surface modifier at 80 volume% based on the volume of the wet gel complex, and surface modification was performed at a temperature of 70°C for 4 hours. After the completion of surface modification, the wet gel complex was placed in a 70L supercritical extractor, and CO2 was injected at 28°C and 70 bar at a rate of 70 L / min for 10 minutes. Subsequently, the temperature inside the extractor was raised to 50°C over 1 hour and 20 minutes, and upon reaching 50°C and 150 bar, CO2 was injected continuously at a rate of 5 L / min for 20 minutes. During this process, ethanol was recovered through the bottom of the separator. Supercritical drying was performed by injecting CO2 continuously at a rate of 5 L / min again for 20 minutes after a 20-minute rest period. Afterwards, CO2 was vented for 2 hours, and a silica aerogel composite was prepared.

[0230] [Experimental Example 1] Volume ratio of fibers and remainder per unit volume of aerogel composite

[0231] The following experiment was performed to determine the volume ratio of the fibers and the remaining parts, that is, the voids between the aerogel containing pores and the dispersed fibers, in the silica aerogel composites prepared in Examples 1 to 5 and Comparative Examples 1 to 5, which were finally dried as described above.

[0232] First, aerogel composites of Examples 1 to 1 and Comparative Examples 1 to 5 were prepared with dimensions of approximately 60 cm x 12 cm in width x length and approximately 0.4 cm in height, and then five rectangular specimens with dimensions of 1 cm x 1 cm in width x length were obtained from each aerogel composite. However, four specimens were obtained by positioning the center of the specimen at a distance of 10 cm from each corner of the aerogel composite in the direction of the center, and one specimen was obtained by positioning the center of the aerogel composite at the center of the specimen.

[0233] Subsequently, the specimen was placed on a DEBEN load cell, the load cell was assembled, and the stage portion of the equipment was modified into a dedicated stage capable of fixing the load cell. At this time, in-situ XRM analysis was performed using a ZEISS VERSA 520 instrument under the conditions shown in Table 1 below. Based on the analysis results, Dragonfly software (version 2021.3) was used to determine the volume ratio of fibers and aerogel, including voids and pores, in the aerogel composite specimen. To aid in understanding the analysis method, the following explanation refers to Figures 1 to 3, which illustrate an example analysis process. After activating the results of the completed in-situ XRM analysis in Dragonfly software, the area to be segmented was set and extracted by adjusting the border using the Clip function (Figure 1). At this time, the size of the segmented area was set to approximately 1700μm X 1600μm X 500μm (width X depth X height). Within the segmented region, fibers and the remaining non-fiber parts were distinguished based on contrast using the lower otsu and upper otsu functions of Dragonfly software (Fig. 2). The lower otsu function identified the segmented region with low contrast corresponding to the non-fiber parts, while the upper otsu function distinguished the segmented region with high contrast corresponding to the fibers. Then, the volume share (volume ratio) of the fibers and the remaining non-fiber parts was calculated using Dragonfly software (Fig. 3). Through the above analysis, the average values ​​of the volume ratio of fibers per unit volume of the aerogel composite and the volume ratio of the aerogel including the voids and pores between the discrete fibers, measured for five specimens for each example or comparative example, were calculated and are shown in Table 2 below.

[0234] Acceleration voltage 80 kV Voxel size 2.5 μm Objective lens magnification 4X Exposure time 1 s / frame Total number of frames 3201

[0235] division Volume ratio of fibers per unit volume of aerogel composite (%) Volume ratio (%) of the remaining portion excluding fibers per unit volume of the aerogel composite Example 1 9.7 90.3 Example 2 7.4 92.6 Example 3 6.5 93.5 Example 4 8.8 91.2 Example 5 8.5 91.5 Comparative Example 1 22.9 77.1 Comparative Example 2 13.6 86.4 Comparative Example 3 15.4 84.6 Comparative Example 4 23.8 76.2 Comparative Example 5 25.4 74.6

[0236] As shown in Table 2 above, the fibers per unit volume of the silica aerogel composites prepared in Examples 1 to 5 are included in an amount of 2 to 12 volume%, and the remaining portion excluding the fibers is the void between the pore-containing aerogel and the dispersed fibers, which is included in an amount of 88 to 98 volume%.

[0238] [Experimental Example 2] Weight ratio of fiber substrate to aerogel in an aerogel composite

[0239] The weight of the silica aerogel composites prepared in Examples 1 to 5 and Comparative Examples 1 to 5, which were finally dried as described above, was measured. In addition, the amount of fiber substrate used in the aerogel composite was subjected to supercritical drying and atmospheric pressure drying in the same manner as in Comparative Example 1, and then its weight was measured. Assuming the difference between the weight of the silica aerogel composite and the weight of the fiber substrate as the weight of the aerogel, the weight ratio of the fiber substrate to the aerogel in each example and comparative example was calculated and is shown in Table 3 below.

[0240] division Fiber: Aerogel weight ratio Example 1 1:0.7 Example 2 1:0.6 Example 3 1:0.45 Example 4 1:0.5 Example 5 1:0.5 Comparative Example 1 1:0.375 Comparative Example 2 1:0.5 Comparative Example 3 1:0.375 Comparative Example 4 1:0.3 Comparative Example 5 1:0.25

[0241] As shown in Table 3 above, in the silica aerogel composites prepared in Examples 1 to 5, the fiber substrate and the aerogel are included in a weight ratio of 1:0.4 to 1.

[0243] [Experimental Example 3] Evaluation of Thermal Stability at High Temperature of 350 ℃

[0244] To evaluate the thermal stability of the aerogel composite prepared according to the present invention at a high temperature of 350°C, the aerogel composites prepared in the above examples and comparative examples were maintained at an isothermal temperature of 350°C for 1 hour, and the weight retention rate of the aerogel composites over time was analyzed. For this analysis, specimens measuring 10 cm x 10 cm were obtained from each of the aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5. Subsequently, the temperature inside the furnace (Changsin Science C-FMD) was heated to 350°C, the above aerogel composite specimens were placed inside and maintained for 1 hour, and the weight loss rate of the specimens compared to the initial state (after heat treatment at 150°C for 1 hour) was measured, and the results are shown in Table 4 below. In addition, to check the variation in weight loss over time, the average value (b) of the weight retention rates measured at 5, 10, 15, 20, 25, and 30 minutes was calculated, and the difference between the weight retention rate (a) and the average value at each time, and the percentage (A) of that difference relative to the average value (b), were calculated and shown in Table 5 below. Note that in Table 5 below, the weight retention rate (a) and the average value (b) were rounded to the second decimal place. The percentage of deviation (A) was rounded to the fourth decimal place.

[0245] [Equation 2]

[0246] A (%) = {(Weight retention rate measured after heating for x minutes (a)) - (Average value of weight retention rates after heating (b))} / (Average value of weight retention rates after heating (b)) X 100

[0247] Example 1 hour (weight%) Weight retention rate Weight loss rate 5 minutes (300 seconds) 98.43 1.57 10 minutes (600 seconds) 98.23 1.77 15 minutes (900 seconds) 98.15 1.85 20 minutes (1200 seconds) 98.09 1.91 25 minutes (1500 seconds) 98.05 1.95 30 minutes (1800 seconds) 98.02 1.98 40 minutes (2400 seconds) 97.96 2.04 50 minutes (3000 seconds) 97.91 2.09 60 minutes (3600 seconds) 97.88 2.12 Example 2 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 99.45 0.55 10 minutes (600 seconds) 99.34 0.66 15 minutes (900 seconds) 99.32 0.68 20 minutes (1200 seconds) 99.28 0.72 25 minutes (1500 seconds) 99.28 0.72 30 minutes (1800 seconds) 99.25 0.75 40 minutes (2400 seconds) 99.23 0.77 50 minutes (3000 seconds) 99.21 0.79 60 minutes (3600 seconds) 99.19 0.81 Example 3 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 99.26 0.74 10 minutes (600 seconds) 99.08 0.92 15 minutes (900 seconds) 98.83 1.17 20 minutes (1200 seconds) 98.62 1.38 25 minutes (1500 seconds) 98.17 1.83 30 minutes (1800 seconds) 97.93 2.07 40 minutes (2400 seconds) 97.77 2.23 50 minutes (3000 seconds) 97.62 2.38 60 minutes (3600 seconds) 97.31 2.69 Example 4 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 98.57 1.43 10 minutes (600 seconds) 98.32 1.68 15 minutes (900 seconds) 98.26 1.74 20 minutes (1200 seconds) 98.18 1.82 25 minutes (1500 seconds) 98.02 1.98 30 minutes (1800 seconds) 97.89 2.11 40 minutes (2400 seconds) 97.73 2.27 50 minutes (3000 seconds) 97.57 2.43 60 minutes (3600 seconds) 97.40 2.60 Example 5 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 98.21 1.79 10 minutes (600 seconds) 98.12 1.88 15 minutes (900 seconds) 98.06 1.94 20 minutes (1200 seconds) 97.99 2.01 25 minutes (1500 seconds) 97.98 2.02 30 minutes (1800 seconds) 97.95 2.05 40 minutes (2400 seconds) 97.90 2.10 50 minutes (3000 seconds) 97.87 2.13 60 minutes (3600 seconds) 97.85 2.15 Comparative Example 1 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 97.50 2.50 10 minutes (600 seconds) 94.66 5.34 15 minutes (900 seconds) 93.82 6.18 20 minutes (1200 seconds) 93.67 6.33 25 minutes (1500 seconds) 93.57 6.43 30 minutes (1800 seconds) 93.50 6.50 40 minutes (2400 seconds) 93.43 6.57 50 minutes (3000 seconds) 93.37 6.63 60 minutes (3600 seconds) 93.32 6.68 Comparative Example 2 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 99.10 0.90 10 minutes (600 seconds) 98.23 1.77 15 minutes (900 seconds) 97.82 2.18 20 minutes (1200 seconds) 97.56 2.44 25 minutes (1500 seconds) 96.87 3.13 30 minutes (1800 seconds) 95.72 4.28 40 minutes (2400 seconds) 94.96 5.04 50 minutes (3000 seconds) 94.76 5.24 60 minutes (3600 seconds) 94.59 5.41 Comparative Example 3 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 99.79 0.21 10 minutes (600 seconds) 98.51 1.49 15 minutes (900 seconds) 97.79 2.21 20 minutes (1200 seconds) 97.13 2.87 25 minutes (1500 seconds) 96.30 3.70 30 minutes (1800 seconds) 95.83 4.17 40 minutes (2400 seconds) 95.12 4.88 50 minutes (3000 seconds) 94.46 5.54 60 minutes (3600 seconds) 94.02 5.98 Comparative Example 4 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 98.63 1.37 10 minutes (600 seconds) 97.46 2.54 15 minutes (900 seconds) 97.01 2.99 20 minutes (1200 seconds) 96.58 3.42 25 minutes (1500 seconds) 96.12 3.88 30 minutes (1800 seconds) 94.97 5.03 40 minutes (2400 seconds) 94.20 5.80 50 minutes (3000 seconds) 93.82 6.18 60 minutes (3600 seconds) 92.79 7.21 Comparative Example 5 hour Weight retention rate Weight loss rate 5 minutes (300 seconds) 97.52 2.48 10 minutes (600 seconds) 96.98 3.02 15 minutes (900 seconds) 96.11 3.89 20 minutes (1200 seconds) 95.62 4.38 25 minutes (1500 seconds) 95.13 4.87 30 minutes (1800 seconds) 94.38 5.62 40 minutes (2400 seconds) 93.77 6.23 50 minutes (3000 seconds) 93.14 6.86 60 minutes (3600 seconds) 92.63 7.37

[0248] Example 1 hour (weight%) Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 98.43 98.16 0.27 0.2751 10 minutes (600 seconds) 98.23 0.07 0.0713 15 minutes (900 seconds) 98.15 -0.01 -0.0102 20 minutes (1200 seconds) 98.09 -0.07 -0.0713 25 minutes (1500 seconds) 98.05 -0.11 -0.1121 30 minutes (1800 seconds) 98.02 -0.14 -0.1426 Example 2 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 99.45 99.32 0.13 0.1309 10 minutes (600 seconds) 99.34 0.02 0.0201 15 minutes (900 seconds) 99.32 0 0.0000 20 minutes (1200 seconds) 99.28 -0.04 -0.0403 25 minutes (1500 seconds) 99.28 -0.04 -0.0403 30 minutes (1800 seconds) 99.25 -0.07 -0.0705 Example 3 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 99.26 98.65 0.61 0.6196 10 minutes (600 seconds) 99.08 0.43 0.4368 15 minutes (900 seconds) 98.83 0.18 0.1828 20 minutes (1200 seconds) 98.62 -0.03 -0.0305 25 minutes (1500 seconds) 98.17 -0.48 -0.4876 30 minutes (1800 seconds) 97.93 -0.72 -0.7313 Example 4 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 98.57 98.21 0.36 0.3666 10 minutes (600 seconds) 98.32 0.11 0.1120 15 minutes (900 seconds) 98.26 0.05 0.0509 20 minutes (1200 seconds) 98.18 -0.03 -0.0305 25 minutes (1500 seconds) 98.02 -0.19 -0.1935 30 minutes (1800 seconds) 97.89 -0.32 -0.3258 Example 5 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 98.21 98.05 0.16 0.1632 10 minutes (600 seconds) 98.12 0.07 0.0714 15 minutes (900 seconds) 98.06 0.01 0.0102 20 minutes (1200 seconds) 97.99 -0.06 -0.0612 25 minutes (1500 seconds) 97.98 -0.07 -0.0714 30 minutes (1800 seconds) 97.95 -0.1 -0.1020 Comparative Example 1 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 97.50 94.45 3.05 3.2292 10 minutes (600 seconds) 94.66 0.21 0.2223 15 minutes (900 seconds) 93.82 -0.63 -0.6670 20 minutes (1200 seconds) 93.67 -0.78 -0.8258 25 minutes (1500 seconds) 93.57 -0.88 -0.9317 30 minutes (1800 seconds) 93.50 -0.95 -1.0058 Comparative Example 2 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 99.10 97.55 1.55 1.5889 10 minutes (600 seconds) 98.23 0.68 0.6971 15 minutes (900 seconds) 97.82 0.27 0.2768 20 minutes (1200 seconds) 97.56 0.01 0.0103 25 minutes (1500 seconds) 96.87 -0.68 -0.6971 30 minutes (1800 seconds) 95.72 -1.83 -1.8760 Comparative Example 3 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 99.79 97.56 2.23 2.2858 10 minutes (600 seconds) 98.51 0.95 0.9738 15 minutes (900 seconds) 97.79 0.23 0.2358 20 minutes (1200 seconds) 97.13 -0.43 -0.4408 25 minutes (1500 seconds) 96.30 -1.26 -1.2915 30 minutes (1800 seconds) 95.83 -1.73 -1.7733 Comparative Example 4 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 98.63 96.80 1.83 1.8905 10 minutes (600 seconds) 97.46 0.66 0.6818 15 minutes (900 seconds) 97.01 0.21 0.2169 20 minutes (1200 seconds) 96.58 -0.22 -0.2273 25 minutes (1500 seconds) 96.12 -0.68 -0.7025 30 minutes (1800 seconds) 94.97 -1.83 -1.8905 Comparative Example 5 hour Weight retention rate (a) Average value (b) Deviation (ab) Percentage of deviation (A(%)) 5 minutes (300 seconds) 97.52 95.96 1.56 1.6257 10 minutes (600 seconds) 96.98 1.02 1.0629 15 minutes (900 seconds) 96.11 0.15 0.1563 20 minutes (1200 seconds) 95.62 -0.34 -0.3543 25 minutes (1500 seconds) 95.13 -0.83 -0.8649 30 minutes (1800 seconds) 94.38 -1.58 -1.6465

[0249] As shown in Tables 4 and 5 above, the aerogel composites according to the present invention (Examples 1 to 5) showed a small weight loss rate after 5 minutes at a high temperature of 350°C and showed almost no change in weight over time; even after a long period of 60 minutes, the weight retention rate was 97% by weight or higher, and the weight loss rate was less than 3% by weight. Furthermore, it was observed that the weight retention rate of the aerogel composites according to the present invention remained almost constant as time elapsed from a relatively short period of 5 minutes to a relatively long period of 30 minutes. However, the aerogel composites of Comparative Examples 1 to 5 showed a continuous decrease in weight during the 60 minutes of analysis, and it was confirmed that the weight loss rate was significantly higher compared to the examples. In addition, it was observed that the weight of the aerogel composites of Comparative Examples 1 to 5 fluctuated with a large deviation during the time elapsed from 5 minutes to 30 minutes.

[0251] [Experimental Example 4] Evaluation of Surface and Cross-sectional Water Repellency

[0252] The following experiment was performed to evaluate the surface and internal hydrophobicity of the aerogel composite prepared according to the present invention.

[0253] 1. Surface water repellency measurement

[0254] First, specimens measuring 10 cm x 10 cm (with a thickness of approximately 4 mm, which is the thickness of the aerogel composite) were obtained from each of the aerogel composites of Examples 1 to 5 and Comparative Examples 1 to 5. After floating the specimens on distilled water at a temperature of 21 ± 2 ℃, a 6.4 mm mesh screen was lowered 127 mm below the water surface (impregnation). After 15 minutes, the mesh screen was removed, and once the specimens floated to the surface, they were clamped and suspended vertically for 60 ± 5 seconds. Subsequently, the weight of the specimens before and after impregnation was measured and calculated according to Equation 4 below, which was expressed as the surface water repellency. A lower surface water repellency value indicates superior hydrophobicity of the silica aerogel composite surface.

[0255] [Equation 4]

[0256] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100

[0257] 2. Measurement of surface water repellency

[0258] Cross-sectional water repellency was measured by cutting a 10cm x 10cm specimen into 1cm x 1cm pieces (with a thickness of approximately 4 mm, which is the thickness of the aerogel composite) using the same method as the surface water repellency described above. However, considering the size of the specimens, five specimens were prepared for each example or comparative example, and the same experiment was repeated for each specimen to determine the cross-sectional water repellency, after which the average value was expressed. The average value was rounded to the second decimal place. Here, a lower cross-sectional water repellency value indicates superior internal hydrophobicity of the silica aerogel composite.

[0259] Surface water repellency (%) Surface water repellency (%) Example 1 1.18 0.76 Example 2 0.75 0.51 Example 3 3.54 1.13 Example 4 3.21 1.15 Example 5 3.6 1.13 Comparative Example 1 4.89 3.75 Comparative Example 2 4.45 2.73 Comparative Example 3 5.64 3.16 Comparative Example 4 9.51 5.51 Comparative Example 5 11.01 6.13

[0260] As shown in Table 6 above, the surface water repellency of the aerogel composites of Examples 1 to 5 according to the present invention is low at approximately 4 wt% or less, and the cross-sectional water repellency is also very low at 1.5 wt% or less. Through this, it was found that the aerogel composite according to the present invention has high surface and internal hydrophobicity and excellent water repellency. On the other hand, the surface water repellency of the aerogel composites of Comparative Examples 1 to 5 is at a level exceeding 4 wt%, and the cross-sectional water repellency is very low at a minimum of 2.73 wt% and a maximum of 6.13 wt%, and in particular, the hydrophobicity inside the aerogel composite is low.

[0262] [Experimental Example 5] Evaluation of Thermal Insulation Performance

[0263] To evaluate the room temperature thermal conductivity of the aerogel composite prepared according to the present invention, the room temperature thermal conductivity of the 60 cm x 12 cm aerogel composites prepared in each example and comparative example was measured using a Netzsch HFM436 instrument, and the results are shown in Table 7 below.

[0264] In addition, to evaluate the thermal conductivity at high temperatures, the aerogel composites prepared in the above examples and comparative examples were subjected to GHP (Guarded Hot Plate) high-temperature thermal conductivity measurements at a temperature of approximately 150°C using a GHP 456 instrument from NETZSCH, and the results are shown together in Table 7 below.

[0265] division Room temperature thermal conductivity (mW / mK) High temperature thermal conductivity (mW / mK) Example 1 20.8 23.8 Example 2 20.5 23.5 Example 3 18.5 21.3 Example 4 17.9 21.1 Example 5 18.7 22.0 Comparative Example 1 21.1 24.7 Comparative Example 2 20.9 24.1 Comparative Example 3 21.3 24.2 Comparative Example 4 23.2 26.2 Comparative Example 5 25.9 29.7

[0266] As shown in Table 7 above, it was found that the aerogel composites of Examples 1 to 5 according to the present invention had superior thermal insulation properties at both room temperature and high temperature compared to the aerogel composites of Comparative Examples 1 to 5.

[0268] [Example 6] Manufacture of an insulating member

[0269] An insulating member was manufactured by attaching ALKYN-1505(C) product from ALKYNES, in which a 25 μm thick acrylic adhesive is applied to one side of a 25 μm thick PET film, to both sides of the aerogel composites prepared in Examples 1 to 5 above.

[0271] [Example 7] Manufacture of an insulating member

[0272] An insulating member was manufactured by attaching ALKYN-4005(FR) product from ALKYNES, in which a 25 μm thick acrylic adhesive is applied to one side of a 25 μm thick flame-retardant PET film, to both sides of the aerogel composites prepared in Examples 1 to 5 above.

[0274] [Example 8] Manufacture of an insulating member

[0275] An insulating member was manufactured by attaching an ALKYN-4004D(PS) product from ALKYNES, in which a 7 μm thick polyester film and a 12 μm thick PET film are sequentially laminated on both sides of the aerogel composite prepared in Examples 1 to 5 above, and a 25 μm thick acrylic adhesive is applied to the other side of the polyester film.

[0277] Foregoing, specific parts of the present invention have been described in detail. It is evident to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the invention. Accordingly, the actual scope of the invention is defined by the appended claims and their equivalents.

Claims

Claim 1 A fiber substrate comprising a plurality of discrete fibers and voids between the fibers; An aerogel composite comprising a plurality of aerogel particles located on the fibers or in the voids between the fibers, and a silica aerogel having a network structure including one or more pores, wherein the weight retention rate measured after heating the aerogel composite at a temperature of 350°C for 60 minutes is 96% or higher, and the weight retention rate measured after heating the aerogel composite at a temperature of 350°C for times of 5, 10, 15, 20, 25, and 30 minutes, respectively, satisfies the following Equation 2, wherein the volume ratio of the fibers per unit volume of the aerogel composite is 2% to 12%, and the volume ratio of the voids between the aerogel containing pores and the discrete fibers per unit volume of the aerogel composite is 88% to 98%, wherein: [Equation 2] A(%) = {(weight retention rate (a) measured after heating for x minutes) - (of weight retention rates after heating { average value (b))} / ( average value of weight retention rates after heating (b)) X 100 In the above Equation 2, the x minutes is 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes, and the weight retention rate (a) measured after heating for the x minutes is the percentage (%) of the weight of the aerogel composite measured after heating the aerogel composite at a temperature of 350 ℃ for x minutes relative to the weight of the aerogel composite before heating at 350 ℃, and the average value of weight retention rates after heating (b) means the average value of the weight retention rates obtained after heating the aerogel composite at a temperature of 350 ℃ for each of the times of 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes, and A is a real number from -1.0 to +1.

0. Claim 2 In claim 1, the aerogel composite, wherein A is a real number from -0.80 to +0.

80. Claim 3 The aerogel composite according to claim 1, wherein the weight retention rate measured after heating the aerogel composite at a temperature of 350°C for 30 minutes is 97% or higher. Claim 4 In claim 1, the aerogel composite satisfies the following Equation 3, wherein the absolute value (B) of the change in weight retention rate of the aerogel composite per unit time when the aerogel composite is heated at a temperature of 350 °C for times of 5 minutes and 60 minutes, respectively: [Equation 3] B = |{(Weight retention rate measured after heating for y minutes) - (Weight retention rate measured after heating for z minutes)} / (y - z)| In the above Equation 3, y is 5 minutes and z is 60 minutes; the weight retention rate measured after heating for y minutes is the percentage (%) of the weight of the aerogel composite measured after heating at 350°C for y minutes relative to the weight of the aerogel composite before heating at 350°C; the weight retention rate measured after heating for z minutes is the percentage (%) of the weight of the aerogel composite measured after heating at 350°C for z minutes relative to the weight of the aerogel composite before heating at 350°C; and B is 1.0 X 10⁻⁶ -3 Up to 7.0 X 10 -2 It is a mistake. Claim 5 An aerogel composite according to claim 1, wherein the volume ratio of the fibers per unit volume of the aerogel composite is 5 to 10%, and the volume ratio of the voids between the aerogel containing pores and the dispersed fibers per unit volume of the aerogel composite is 90 to 95%. Claim 6 The aerogel composite according to claim 1, wherein the fiber substrate and the silica aerogel within the aerogel composite are included in a weight ratio of 1:0.4 to 2. Claim 7 The aerogel composite according to claim 1, wherein the silica aerogel comprises silica, methylsilylated silica, dimethylsilylated silica, trimethylsilylated silica, or a mixture thereof. Claim 8 In claim 1, the aerogel composite is an aerogel composite having a moisture impregnation rate (weight%) of 4 weight% or less for a specimen of size 100 mm X 100 mm represented by the following formula 4: [Formula 4] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100 In the above formula 4, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes. Claim 9 In claim 1, the aerogel composite is an aerogel composite having a moisture impregnation rate (weight%) of 2 weight% or less for a specimen of size 10 mm X 10 mm represented by the following formula 4: [Formula 4] Moisture impregnation rate (weight%) = {(Weight of specimen after impregnation - Weight of specimen before impregnation) / (Weight of specimen before impregnation)} X 100 In the above formula 4, the weight of the specimen after impregnation refers to the weight of the aerogel composite specimen after impregnating it in distilled water at 21±2 ℃ for 15 minutes. Claim 10 An insulating member comprising the aerogel composite of claim 1. Claim 11 In claim 10, the insulating member further comprises a supporting member positioned on at least one of the upper and lower surfaces of the aerogel composite. Claim 12 A battery module comprising a module case having an internal space, one or more battery cells located in the internal space, and an aerogel composite of claim 1 located in the internal space. Claim 13 A battery pack comprising the battery module of claim 12. Claim 14 delete Claim 15 delete Claim 16 delete

Citation Information

Patent Citations

  • Method for preparing aerogel blanket and aerogel blanket prepared by the same

    KR1020170104956A

  • Composite articles comprising aerogel particles, ceramic and / or glass fibers, and opacifiers

    KR1020230154800A

  • Method for producing aerogel blanket and aerogel blanket produced thereby

    US11274044B2

  • Aerogel-based components and systems for electric vehicle thermal management

    US20210163303A1

  • Composite article comprising aerogel particles and ceramic fibers

    US20230212079A1